The Experience of Tinnitus and Its Interaction With Unique Life Histories—Life Events, Trauma and Inner Resources Narrated by Patients With Tinnitus - Erlandsson, Soly Inga-Maj; Lundin, Linda; Dauman, Nicolas (Frontiers in Psychiatry, 2020)
Background: The challenges facing people with chronic tinnitus include finding relief and rebuilding quality of life. However, previous traumatic episodes may influence adjustment and prolong suffering. Recovery implies reducing aggravating reactions and improving social roles, relationships and interests. Self-narratives about living with tinnitus have not yet received the attention they deserve in the research literature. Thus, the main goal of the present study was to illustrate how tinnitus suffering interacts with the participants' unique life histories. Method: Four women and one man (ages 52–58) took part in the study after consulting a special hearing clinic for annoying tinnitus. Criteria for inclusion were that tinnitus was regarded as a problem with negative consequences for quality of life. The participants should be willing to share how the experience of tinnitus suffering interacts with their previous life story. Narrative methodology was employed in order to achieve the goals of the study. We used unstructured interviews with free conversation, which allowed for rich narratives with full contextual meaning. Results: The findings, based on the narrative analysis, revealed that three out of five participants presented a regressive form of narrative indicating ongoing struggles beyond tinnitus itself, which they were unable to bring to closure. For them, valued goals were continuously thwarted by frustrating circumstances in their lives, either past events or current unresolved issues. Progressive and stable narratives, as identified in the other two participants, demonstrated values that rely on others' attitude and understanding toward their suffering, in sharp contrast to the regressive narratives. We suggest that a central issue in tinnitus rehabilitation should be to help suffering patients to overcome unresolved conflicts and thereby extend their ability for a fuller commitment in life. Conclusion: Considering enduring tinnitus as a chronic condition, whose course is likely to vary depending on the patient's general health status, an alteration of progressive and stable narratives is likely to occur during the lifespan. A progressive narrative shows similarities to the core construct of the salutogenesis model of health promotion (1). In conclusion, a narrative approach in tinnitus rehabilitation can be health promoting by offering the patient the opportunity to engage in storytelling, which in turn can increase comprehensibility and a sense of coherence.